(untitled) - Martin, Judith N. (New York, 2005)
This introductory text covers the core concepts of intercultural communication and offers students a basic skill-building framework designed to be used every day for communicating across cultures. By using the "building blocks" of the framework in different ways, students will understand the complexities of intercultural interaction and learn about other cultures as well as their relationships with their own culture.
Keywords: Intercultural communication,Truyền thông liên văn hóa